To Lose Both Would Look Like Carelessness: Tasmanian Devil Facial Tumour Disease - McCallum, Hamish; Jones, Menna (PLOS Biology, 2006)
How can you manage an emerging disease threat--in this case, Tasmanian devil facial tumor disease--that poses a serious conservation threat, when so little is known about the disease?